ANALISIS FAKTOR - FAKTOR YANG MEMPENGARUHI UNDERPRICING SAHAM PADA PENAWARAN SAHAM PERDANA DI BURSA EFEK INDONESIA PERIODE 2012-2014 - Dita Pratana Ayusari, 12.05.52.0158; Puspitasari, Elen (Students Journal of Accounting and Banking, 2016)
This study examines the factors that affect underpricing shares at the initial public offering. This research was conducted at the Indonesian Stock Exchange (BEI) by using analysis of manufacturing and non-manufacturing companies. The sampling method using purposive sampling with the period from 2012 to 2014. The relationship between variables and or described by using multiple regression analysis. The results showed that the underwriter reputation variables significant negative effect on underpricing shares. While the variable auditor reputation and size of the company and no significant positive effect on underpricing shares. In the variable age of the firm, the companys profitability, financial leverage, and the type of industry and no significant negative effect on underpricing shares. However, earnings per share positive and significant effect on underpricing shares.Keywords: Underwriter Reputation, Reputation Auditor, Age Company, Company Size, Profitability Companies, Financial Leverage, Earnings Per Share, Type of Industry, and Underpricing Shares